APPLICATION OF UZBEK IKAT IN MODERN CLOTHING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article examines the features of using Uzbek ikat in modern fashion design. It explores its historical origins, artistic characteristics, and technological aspects of production. Particular attention is paid to the trends of the 21st century associated with the revival of interest in national textiles and ethnic motifs in fashion. Based on the analysis of the work of contemporary designers and fashion brands, the study reveals ways of integrating traditional Uzbek patterned weaving into the modern fashion industry. The role of ikat in shaping cultural identity and promoting the sustainable fashion movement is emphasized.